Research-informed decision-making for empowering integrated care system development: Co-creating innovative solutions to facilitate enhanced service provision - Eren Demir; Usame Yakutcan; Stephen Page (PLoS ONE, 2025)
Integrated care has emerged as a vital approach to addressing complex health and social care challenges through attempting to foster collaborative provision in healthcare settings. Yet as demand for services often outstrips supply, hospitals, as anchor institutions in communities, are constantly seeking to innovate to align their resources with needs and policy priorities. As hospitals are often viewed as a conduit for creating and embracing innovation to enhance organisational performance, this paper outlines one such innovation, which was co-created as a partnership between a university and hospital to help it with its transition to an integrated care system (ICS). By developing a full hospital system model in partnership not only with hospital stakeholders but also out-of-hospital services - such as community and primary care - for an integrated care model, this study helps to translate an innovative model into practice at an ICS level. To achieve this, decision support tools (DSTs) were used to foster evidence-based assessment of the hospital system, and key opinion leaders (KOLs) were provided with a versatile toolset with which to optimise workforce productivity and deployment, innovate service provision, and enhance community health.